2019
DOI: 10.3390/biology8010010
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Peripheral Nerves in Adipose Tissue for the Regulation of Energy Balance

Abstract: Brown and white adipose tissues are essential for maintenance of proper energy balance and metabolic health. In order to function efficiently, these tissues require both endocrine and neural communication with the brain. Brown adipose tissue (BAT), as well as the inducible brown adipocytes that appear in white adipose tissue (WAT) after simulation, are thermogenic and energy expending. This uncoupling protein 1 (UCP1)-mediated process requires input from sympathetic nerves releasing norepinephrine. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 165 publications
(264 reference statements)
0
36
0
1
Order By: Relevance
“…Nerves also rely on vasculature for sustained health, since they become damaged in a hypoxic state, while vasculature relies on innervation for constriction and vasodilation of blood vessels. Since nerves, such as those in the sympathetic nervous system, regulate vascular control (ie: vasoconstriction) and may also be involved in angiogenesis, adipose neuropathy may also have adverse effects on endocrine system communication with adipose tissue and may lead to adipose hypoxia due to lack of proper vascular supply [48]. The association here could also go in the other direction, with circulating factors affecting nerve supply (ie: glucose, lipids, hormones)–but these hypotheses require closer investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Nerves also rely on vasculature for sustained health, since they become damaged in a hypoxic state, while vasculature relies on innervation for constriction and vasodilation of blood vessels. Since nerves, such as those in the sympathetic nervous system, regulate vascular control (ie: vasoconstriction) and may also be involved in angiogenesis, adipose neuropathy may also have adverse effects on endocrine system communication with adipose tissue and may lead to adipose hypoxia due to lack of proper vascular supply [48]. The association here could also go in the other direction, with circulating factors affecting nerve supply (ie: glucose, lipids, hormones)–but these hypotheses require closer investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, it has been demonstrated that the levels of gamma-aminobutyric acid (GABA), an inhibitory neurotransmitter that suppresses neuron excitability, are increased in BAT of HFD-fed mice promoting BAT disfunction [118]. All these exiting results provide new insights into innervation patterns and nerve plasticity in adipose depots, suggesting that neuromodulation could become an essential strategy to explore new ways to treat obesity (reviewed in [119][120][121][122]). Additional research should be done to elucidate nerve subtypes and their tissue functions in order to understand the physiological crosstalk between brain and peripheral tissues and their contribution to maintain energy balance.…”
Section: Physiological Mechanisms Involved In Diet-induced Obesitymentioning
confidence: 99%
“…Norepinephrine (NE) released from SNFs activates the β-adrenergic receptor (βAR)-cyclic AMP/protein kinase A (cAMP/PKA) signaling pathway to induce these morphological and thermogenic changes during cold stimulation ( Ceddia and Collins, 2020 ; Li et al, 2016 ). Accordingly, denervation of iWAT depots blocks cold-induced thermogenesis and the appearance of beige adipocytes ( Blaszkiewicz et al, 2019 ; Harris, 2018 ). Overall, activation of this β-adrenergic pathway to modulate adipose tissue composition and functions yields increased glucose tolerance and resistance to high-fat-diet (HFD)-induced insulin resistance ( Ceddia and Collins, 2020 ; Collins, 2012 ).…”
Section: Introductionmentioning
confidence: 99%